Metachronous venous malformation masquerading as an obscure gastrointestinal bleed - Neehar Patil; Jeevak Shetty; Padmalatha S Kadamba; Manjiri Somashekhar; M K Kalpana Kumari (Wolters Kluwer Medknow Publications, 2022)
Vascular malformation of the gastrointestinal (GI) tract along with metachronous lesions elsewhere in the body is extremely rare. We report an unusual case of a female child, with a history of venous malformation excision over the right leg presenting with severe iron-deficiency anemia. Although venous malformations of the small bowel are a rare cause of occult GI bleed, in the presence of cutaneous vascular lesions, there should be a high index of suspicion of a vascular malformation, along with the other causes of GI bleed in children.